IMPROVING HEALTCARE SERVICES USING MOBILE TECHNOLOGY: NEEDS AND EXPECTATION ASSESSMENT FOR THE DEVELOPMENT OF MOBILE HEALTH APPS FOR MENTAL HEALTH SERVICES IN TECHNOLOGY - Slametiningsih Slametiningsih; Ninik Yunitri; Hendra Hendra; Nuraenah Nuraenah; Abdu Rahim Kamil (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2020)
The number of electronic health applications is increasing, including those that can be used for mental health. Previous studies showed that, use of several applications provides great benefits for mental health and greatly increases accessibility to mental health services. The objectives of this study were to assess needs and expectations of patients with mental disorder and a broad group of stakeholders with the expected end product being a well-functioning user-centered technology-based tool for mental disorders. The research was carried out by involving 80 patients with schizophrenia and 74 family’s caregivers in health services and local offices of health services in five cities of Indonesian capital city, Jakarta. This study was conducted through self-administered questionnaires and interviews where possible from December 2017 to July 2018. A descriptive statistic using proportion was used to present the data. The results indicated that patients needed information relevant to disease, patient care, check-up schedules and consultation with health workers. In addition, patients also wanted to get information on job vacancies due to many of them were unemployed and rehabilitation programs carried out by local health services. This study highlighted the needs to develop a mobile-based application for continuity of mental health services in the community.